MOLECULAR DIVERSITY AND PHYLOGENY OF TRITICUM-AEGILOPS SPECIES POSSESSING D GENOME REVEALED BY SSR AND ISSR MARKERS - Moradkhani, Hoda; Mehrabi, Ali Ashraf; Etminan, Alireza; Pour-Aboughadareh, Alireza (Plant Breeding and Seed Science, 2015)
The aim of this study is investigation the applicability of SSR and ISSR markers in evaluating the genetic relationships in twenty accessions of Aegilops and Triticum species with D genome in different ploidy levels. Totally, 119 bands and 46 alleles were detected using ten primers for ISSR and SSR markers, respectively. Polymorphism Information Content values for all primers ranged from 0.345 to 0.375 with an average of 0.367 for SSR, and varied from 0.29 to 0.44 with the average 0.37 for ISSR marker. Analysis of molecular variance (AMOVA) revealed that 81% (ISSR) and 84% (SSR) of variability was partitioned among individu-als within populations. Comparing the genetic diversity of Aegilops and Triticum accessions, based on genetic parameters, shows that genetic variation of Ae. crassa and Ae. tauschii species are higher than other species, especially in terms of Nei’s gene diversity. Cluster analysis, based on both markers, separated total accessions in three groups. However, classification based on SSR marker data was not conformed to classification ac-cording to ISSR marker data. Principal co-ordinate analysis (PCoA) for SSR and ISSR data showed that, the first two components clarified 53.48% and 49.91% of the total variation, respectively. This analysis (PCoA), also, indicated consistent patterns of genetic relationships for ISSR data sets, however, the grouping of acces-sions was not completely accorded to their own geographical origins. Consequently, a high level of genetic diversity was revealed from the accessions sampled from different eco-geographical regions of Iran.